PERAN FUNGI MIKORIZA ARBUSKULA DAN PUPUK ROCK FOSFAT TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max (L.) Merrill) - Ratih Dewi Rengganis; Yaya Hasanah; Nini Rahmawati (Jurnal Agroekoteknologi, 2014)
The objective of the research was to study to determine the effect of arbuscular mychorrhizal fungi(AMF). This research conducted at society field Setiabudi, Medan Tuntungan, in May-July2013using factorial randomized block design with two factor. The first factor wasaplication of AMF (0,20, 40, g/plant). The second factor was aplication of rock phosphate fertilizer (0, 50, 100, 150kg/ha). Variable observed consistedinfection degree of AMF,shoot dry weight,root dry weight andweight of dry seeds.The result showed that AMFeffect significantlyinfection degree of AMF, shootdry weight, root dry weight. Dose of rock phosphate fertilizer affect significantly,infection degreeof AMF, and weight of dry seeds. There is not significantly interaction between AMF and rockphosphate fertilizer for all variable observed.Based on the research results of the AMF dose(20g/plant) and rock phosphate fertilizer (150 kg/ha) can increase on soybean growth and production.Keywords: arbuscular mychorrhizal fungi,rock phosphate fertilizer, soybean